2017
DOI: 10.1017/nws.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

“The framily plan”: Characteristics of ties described as both “friend” and “family” in personal networks

Abstract: Despite the growing potential for multiplexity in our complex social world, social network methodology often does not adequately capture this phenomenon. Most commonly in research on egocentric social networks, when respondent designate a tie as both family member and friend, the tendency is to default to “family” prior to aggregation for analysis, potentially ignoring important and meaningful variation. As a result, relatively little is known about multiplexity in personal social networks, and particularly ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…This is roughly the same in 1997 and 2018, but we do note a decrease in the willingness to consider friends as family members in 2018. This suggests that the idea of framily situations, in which friends are perceived to be family, is not at play here, adding to the recent literature on this subject (Bush et al, 2017).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…This is roughly the same in 1997 and 2018, but we do note a decrease in the willingness to consider friends as family members in 2018. This suggests that the idea of framily situations, in which friends are perceived to be family, is not at play here, adding to the recent literature on this subject (Bush et al, 2017).…”
Section: Resultsmentioning
confidence: 73%
“…Recent evidence of changing perceptions about family can be found in studies on the boundaries between families and other types of relational ties. Bushet al (2017) have found that blurring boundaries between friends and families is increasingly common, which points to a need for more nuanced classifications of families. They stated that “ties characterized as both friends and family members may function more like one or the other type of relationship, introducing complexity and unexplained variation … between roles” (p. 96).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the social role relations employed here might not have been exhausted enough to capture the nuanced interplay between network size and roles. There is growing acknowledgment that social relations can be multiplex (Bush, Walker, & Perry, 2017). Third, future studies could include exchanged social support, also studied for kin and nonkin ties separately.…”
Section: Discussionmentioning
confidence: 99%